Beefing Up Biosecurity: Survey of Ticks (Acari: Ixodidae) Currently Threatening the Tennessee Beef Cattle Industry, and a Proposed Monitoring Strategy for Invasive Ticks. Issue 6 (23rd August 2018) - Theuret, D P; Trout Fryxell, R T
Abstract: Tick-borne diseases are poised to devastate the North American cattle industry if infected ticks invade the country either by importation of an infested-animal or with natural host migration. Our research objectives were to identify sources for invasive-tick monitoring and use those sources to describe seasonal and regional impacts on infestation prevalence and burden of ticks on beef cattle. Throughout the state of Tennessee, we sampled 25% of the total herd size (or 10 animals) at three university-operated research and education centers (RECs) (sentinel sites), six livestock auctions (check-stations), and nine Extension agents at 21 producer locations (tick scouts) from 2015 to 2016. From 1, 817 sampled cattle 740 ticks (Acari: Ixodidae) were collected including 573 Amblyomma americanum (L.) (77.4%), 125 A. maculatum Koch (16.9%), 35 Dermacentor variabilis (Say) (4.7%), and 3 Ixodes scapularis (Say) (0.4%). Western and middle Tennessee were significantly different in infestation prevalence and burden of A. maculatum . For A. maculatum and the species total, infestation prevalence and burden were greater in spring than fall. Auctions (check stations) and RECs (sentinels) had the greatest infestation prevalence of A. maculatum, and the greatest burden of A. maculatum and D. variabilis . High-risk locations clustered in western and middle Tennessee, with low-risk locations in middle and eastern Tennessee. Results from this study provide knowledge necessary to initiate control measures, including seasonal phenology and regional distribution of current tick threats. Use of RECs as sentinel sites and routine tick surveillance at livestock auctions serving as check stations should be used for mitigating invasive tick threats.